EFFECT OF CROP DIVERSIFICATION ON THE LIVELIHOOD OF ARABLE CROP FARMERS IN KWARA STATE, NIGERIA - Ambali, O. Y.; Taiye, A.; Ayantoye, K.; Abdullahi, M. J. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the effect of crop diversification on the livelihood of arable crop farmers in Kwara State, Nigeria. Using a three-stage sampling technique, primary cross-sectional data were collected from 208 respondents via a well-structured questionnaire. Data were analyzed using descriptive statistics and multiple regression analysis. Results revealed that farmers in the study area were predominantly experienced middle-aged farmers with an average of 20 years of farming experience and 44 years of age. Most had a land size of less than 5ha, with the average being 6.5ha, and mostly had secondary education. Most of the farmers (67.8%) diversified into cereals, legumes and tubers for proper risk management. Multiple regression revealed that the number of crops grown (p=0.014), diversification into cereal and legumes (p=0.063), diversification into cereals and tubers (p=0.001), household size (p=0.010), level of education (p=0.040), and access to extension service (p=0.006) all have a significant positive impact on farmers’ livelihood. The study concludes that crop diversification significantly improves livelihood outcomes and recommends that extension access, credit access, education, and climate-resilient policies should be prioritized to promote sustainable adoption among arable crop farmers in Kwara State.